The role of CREB and MAPK signaling pathways in ATLL patients - Akbarin, Mohammad Mehdi; Rezaee, Seyed Abdolrahim; Farjami, Zahra; Rahimi, Hossein; Rafatpanah, Houshang (AIDS research and therapy, 2024)
HTLV-1 is a worldwide distribution retrovirus with 10-20 million infected individuals. ATLL is an Adult T-cell leukaemia lymphoma caused by aggressive T-cell proliferation that is infected by HTLV-1 and is associated with an inferior prognosis. The exact molecular pathogenesis has yet to be fully understood. CREB, a transcription factor, acts as a molecular switch that controls the expression of numerous genes in response to various extracellular signals. Its activation is primarily mediated through phosphorylation by multiple kinases, including MAPKs. MAPKs, a family of serine/threonine kinases, serve as crucial mediators of intracellular signaling cascades. This study investigated, 38 HTLV-I-infected individuals, including 18 HTLV-1 asymptomatic carriers (ACs) and 20 ATLL subjects. mRNA was extracted and converted to cDNA from Peripheral blood mononuclear cells (PBMCs), and then the expression of TAX, HBZ, CREB, and MAPK was analyzed by TaqMan qPCR. The genomic HTLV-1 Proviral loads were examined among the study group. The data analysis showed a significant difference in the mean of CREB expression amongst study groups (ATLL and carriers, (p = 0.002). There is no statistical difference between the MAPK gene expression (p = 0.35). HBZ, TAX, and HTLV-1 proviral load weree significantly higher in ATLL subjects compared to  ACs  (p = 0.002, 0.000, and 0.000), respectively. Moreover, our results, demonstrated a direct positive correlation among HBZ, CREB, and TAX gene expression in ATLL patients (p = 0.001), whilst between the  ACs, TAX gene expression had a positive significant correlation with HBZ and HTLV-1 proviral load (p = 0.007 and p = 0.004, respectively). The present study demonstrated that CREB gene expression was higher in the ATLL group than ACs, while there was no difference for MAPK. Therefore, this pathway may not strongly involve in the activation of CREB. The CREB may be a prognostic factor for the development of HTLV-I-associated diseases and can be used as a monitoring marker for the efficiency of the therapeutic regime and prognosis.